Ultrafast preparation of NiFe nanocluster/graphene heterojunction catalysts for oxygen evolution reaction and urea oxidation reaction. Issue 6 (16th January 2023) - Ge, Xuening; Yin, Long; Zhang, Ling; Shi, Chuanxin; Shen, Qi; Ma, Wenguang; Yang, Xiaodong; Sun, Yiqiang; Li, Cuncheng
Abstract : Developing low-cost and highly efficient oxygen evolution reaction (OER) and urea oxidation reaction (UOR) electrocatalysts is critically important for hydrogen production through electrochemical water splitting. Abstract : Developing low-cost and highly efficient oxygen evolution reaction (OER) and urea oxidation reaction (UOR) electrocatalysts is critically important for hydrogen production through electrochemical water splitting. Herein, ultrasmall NiFe-LDH NCs anchored with high density on the surface of graphene oxide (NiFe NCs/GO) were prepared via an ultrafast (5 s) one-step preparation method. The obtained NiFe NCs/GO exhibited exceptional activity for OER and UOR with a current density of 10 mA cm −2 at low overpotentials of 231 mV and 130 mV, respectively, in basic conditions due to the high inherent catalytic activity of NiFe LDH and the strong coupled interface between the NiFe-LDH NCs and GO substrate. Our work may provide a new ultrafast avenue for preparing highly efficient OER and UOR catalysts.